Anaesthetic Management of Congenital Lobar Emphysema- A Case Report - Ajay S Shandilya; Anil Kumar Narayan; Harini Krishna; Ramya (JCDR Research and Publications Pvt. Ltd., 2022)
Congenital Lobar Emphysema (CLE) is a rare congenital disorder causing overinflation of a lobe or lobes of the lung. The left upper lobe is most commonly involved. Surgery is the preferred treatment in cases of CLE, with the patients recovering well after surgery, even with excision of more than one lobe. Here authors report a case of 2-week-old female infant with worsening respiratory distress that did not resolve despite supplemental oxygen and non-invasive ventilatory support and was subsequently diagnosed with Congenital Lobar Emphysema (CLE). The pathology in CLE is the overinflation of the affected lobes and consequent collapse of the normal lobes, leading to hypoxia and reduced gas exchange. The emphysematous lobe causes the mediastinum to shift to the other side, and severe cases may have a haemodynamic compromise. Anaesthesia in such infants is a precarious proposition. The infants may also have other congenital abnormalities. Furthermore, the over distended lobe will cause several problems affecting the infant's cardiorespiratory physiology. Hence, the preanaesthetic evaluation, anaesthesia plan and execution should be meticulously planned.